Answer :

Assume x = tanθ


= tan–1


= tan–1


= tan–1


= tan–1


= tan–1


Cos θ = 2 cos2 –1 and sinθ =


1 + cosθ = 2 cos2


= tan–1


= tan–1


= tan–1(cot)


cot = tan


= tan–1(tan)


But θ = tan–1x.



Therefore, the simplification of given equation is


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers